Rapid Separation of 94,95Sr - CUI Chun-sheng; DING You-qian; WANG Xiu-feng; BAI Long; ZHOU Zi-jun (He huaxue yu fangshe huaxue, 2023)
In order to accurately measure the decay data of 94,95Sr, it is necessary to prepare 94,95Sr samples with high activity and high purity. To remove or reduce other radioactive isotopes of strontium in the fission product system, based on the analysis of the cumulative yield and half-life of each nuclide in the relevant decay chain, the separation mode of “Short-time irradiation and rapid separation” is adopted, and the chemical process for rapid separation of 94,95Sr is established by combining the rapid extraction of P204 extraction chromatography with the rapid purification of Sr-Spec extraction chromatography, a modular rapid chemical separation device is developed. The total operation time of the device is no more than 60 s, the chemical recovery rate is 40%, and the decontamination factor for the main interfering nuclides can reach more than 102, meeting the requirements of decay data measurement.